Legal Protection in Foreign Exchange Trading Activities with Profitable Strategies - Heryanty Hasan (Universitas Muhammadiyah Palu, 2024)
Foreign exchange trading is used free floating system and does not use fixed rate system or fixed exchange rate as stipulated at the International Conference